Physiological Characteristics of Putative Enterobacteria Associated with Meat and Fish Available in Southern Brazilian Retail Markets: Antimicrobial Susceptibility, Toxic Metal Tolerance and Expression of Efflux Pumps - Renata da Costa Barros Silva; Jéssica Andrade; Vanessa Cordeiro Dias; Jéssica Carla Sequeto; Nayara Felga Santos; Vânia Lúcia da Silva; Cláudio Galuppo Diniz (Antibiotics, 2022)
Multidrug-resistant (MDR) mesophilic facultatively anaerobic Gram-negative rods are a public health issue and their spread from animal-source foods to humans is of concern worldwide. Hence, the aim of this study was to examine the antibiotic susceptibility patterns and physiological aspects of such rods, including their tolerance to toxic metals and the screening of efflux pumps expressing isolates among enterobacteria isolated from meat (chicken, beef and pork) and fish samples acquired from retail establishments in a Brazilian urban Centre of over 2,300,000 inhabitants. The study revealed that 62.9% of isolated bacteria were resistant to at least one antimicrobial, of which 32.3% and 8.1% were resistant to one and two of the tested drugs, respectively. A resistance of up to six antimicrobials was also observed (0.9%). Out of the total amount, 22.7% were classified as MDR. Chicken was the meat that harbored most MDR isolates, and fish harbored the least. It was not possible to distinguish the different types of meat or fish considering the resistance patterns. The MDR isolates showed a higher tolerance to mercury and cadmium salts and the increased activity of the efflux mechanisms compared to other susceptible or resistant strains. In One Health. the perspective occurrence of putative MDR bacteria in fresh meat and fish draws attention to the antimicrobial resistance phenomenon in an open environment.